8(x-9)=12

Simple and best practice solution for 8(x-9)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-9)=12 equation:


Simplifying
8(x + -9) = 12

Reorder the terms:
8(-9 + x) = 12
(-9 * 8 + x * 8) = 12
(-72 + 8x) = 12

Solving
-72 + 8x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '72' to each side of the equation.
-72 + 72 + 8x = 12 + 72

Combine like terms: -72 + 72 = 0
0 + 8x = 12 + 72
8x = 12 + 72

Combine like terms: 12 + 72 = 84
8x = 84

Divide each side by '8'.
x = 10.5

Simplifying
x = 10.5

See similar equations:

| -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 | | 6x-8=6(x-5) | | 23=8*1+y | | 6460-h=4181 | | 1/4=b=3.4 | | 4.6d=26.68 | | 16x-6x=56 |

Equations solver categories